Keefektifan Trichoderma viride TNU dalam Menghambat Infeksi Phytophthora palmivora pada Kakao - Samsudin Samsudin; Rita Harni; Efi Taufik (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Phytophthora palmivora is a pathogenic fungus that causes pod rot and stem cancer in cacao plant. This pathogen was difficult to control because it survives in the form of mycelium and chlamydospores in infected plant parts or in soil. Trichoderma viride is expected to inhibit the growth and development of this pathogen. The study aimed to determine the effectiveness of T. viride in inhibiting P. palmivora infection on cacao, conducted at Plant Protection Laboratory and Greenhouse of Indonesian Industrial and Beverage Crops Research Institute (IIBCRI), Sukabumi from March to December 2014. The T. viride TNU isolates used was purified and propagated in the laboratory. The T. viride inhibition against P. palmivora growth and development was tested in vitro on potato dextrose agar medium (PDA) and in vivo on infected cacao pods and seedlings. The parameters observed were percentage of inhibition on PDA and the disease progression on infected pods and seedlings. The results showed that T. viride inhibited the growth of P. palmivora with inhibition percentage up to 68.60%, a strong antagonist for P. palmivora on PDA and reduced P. palmivora infection on seedlings in the greenhouse. Applications of T. viride 3 days before or after inoculation with P. palmivora was able to protect cacao seedlings in polybags, respectively by 60% and 45%. However, T. viride has not been able to hinder the development of pod rot disease on cacao.